Description of the Prophet (PBUH) in the Poems of Mahwi - Agha Baba, Awat Muhamad; Hamagharib, Bahra Salam; Hamafaraj, Dilan Salam; Abdulla, Kanyaw Bakr; Mahmood, Hemn Mohammed Ali; Ali, Sozan Mahmud; Aziz, Fenk Majed (Raden Intan State Islamic University of Lampung, Indonesia, 2023)
The research is entitled “Description of the Prophet (PBUH) in the poems of Mahwi”, which discusses